Effectiveness of a school health education program (Research, Society and Development, 2022)
Objective: To evaluate the effectiveness of a health education program in schoolchildren aimed at preventing helminth diseases from the perspective of the acquisition of knowledge and skills that favored changes and improvements in quality of life. Method: This is research with epidemiological design of intervention of the type prophylactic clinical trial. Results: The study was conducted in a public school in the city of João Pessoa / Paraíba and included in the data collection adolescents aged 10 to 14 years, enrolled in the 6th and 7th grade of Elementary School II. The results indicate that after performing a health education intervention, the number of correct answers related to the transmission of diseases was: Ascariasis (86.7%) and Hookworm (87.4%). One year after the educational intervention, the results remained positive for Ascariasis and Hookworm (74.1%) with statistical significance. The use of several active methodologies in communication with the target audience was significant to capture attention and build interaction spaces to enhance knowledge sharing. Conclusion: The results indicate that the proposed model of intervention in health education was effective in the moments after the intervention and one year of its accomplishment. The low cost of carrying out the proposed interventions strengthens the indication of their use, given the poor access to materials that some public schools find. Thus, the use of active methodologies can be recommended for health education interventions for students in this age group.